Cysteine-specific protein multi-functionalization and disulfide bridging using 3-bromo-5-methylene pyrrolones - Zhang, Yingqian; Zang, Chuanlong; An, Guoce; Shang, Mengdi; Cui, Zenghui; Chen, Gong; Xi, Zhen; Zhou, Chuanzheng (Nature communications, 2020)
Many reagents have been developed for cysteine-specific protein modification. However, few of them allow for multi-functionalization of a single Cys residue and disulfide bridging bioconjugation. Herein, we report 3-bromo-5-methylene pyrrolones (3Br-5MPs) as a simple, robust, and versatile class of reagents for cysteine-specific protein modification. These compounds can be facilely synthesized via a one-pot mild reaction and they show comparable tagging efficiency but higher cysteine specificity than the maleimide counterparts. The addition of cysteine to 3Br-5MPs generates conjugates that are amenable to secondary addition by another thiol or cysteine, making 3Br-5MPs valuable for multi-functionalization of a single cysteine and disulfide bridging bioconjugation. The labeling reaction and subsequent treatments are mild enough to produce stable and active protein conjugates for biological applications. Many reagents have been developed for cysteine-specific protein modification. However, few of them allow for multi-functionalization of a single Cys residue and disulfide bridging bioconjugation. Here the authors report 3-bromo-5-methylene pyrrolones as a simple, robust and versatile class of reagents for cysteine-specific protein modification.